Asal Usul dan Implementasi Ahli Waris Pengganti Perspektif Hukum Islam - M., Hajar (UIN Sunan Kalijaga, 2016)
The existence of substitute heir still causes polemics either in the side of its derivation or in its validity.The substitute heir in KHI is formulated through yurisprudence which is taken from customary law. The substitute heir in customary law is an adoption of civil law (BW) of Dutch derived from Code Civil Napoleon in French. French’s civil law was born of romen’s law.The substitute heir develops toovercome the matters partaining to inheritance either in the level ofheir, traditional deliberation, or judicature institution. The substitute heir is a culture which is not based on faith, contrary to judicature principle, ijbari basic, not accordance with the elements pertaining inheritance and it is also contrary to superiority and hijab principle. Therefore, it needs to review.